Federated ensemble-learning for transport mode detection in vehicular edge network - Alam, MD. Mustakin; Ahmed, Tanjim; Hossain, Meraz; Emo, Mehedi Hasan; Islam Bidhan, Md. Kausar (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.